2004
DOI: 10.1002/prot.20149
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of eight docking tools for docking and virtual screening accuracy

Abstract: Eight docking programs (DOCK, FLEXX, FRED, GLIDE, GOLD, SLIDE, SURFLEX, and QXP) that can be used for either single-ligand docking or database screening have been compared for their propensity to recover the X-ray pose of 100 small-molecular-weight ligands, and for their capacity to discriminate known inhibitors of an enzyme (thymidine kinase) from randomly chosen "drug-like" molecules. Interestingly, both properties are found to be correlated, since the tools showing the best docking accuracy (GLIDE, GOLD, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
541
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(568 citation statements)
references
References 52 publications
19
541
0
8
Order By: Relevance
“…Identifying inhibitors by virtual screening involves multiple steps, and its success depends on several factors: the efficiency of ligand and receptor conformational sampling (4)(5)(6)(7)(8)(9)(10)(11), the quality of the scoring function (12,13), the choice of docking pocket, and finally, the availability of a relevant assay to test the virtual screening candidates.…”
mentioning
confidence: 99%
“…Identifying inhibitors by virtual screening involves multiple steps, and its success depends on several factors: the efficiency of ligand and receptor conformational sampling (4)(5)(6)(7)(8)(9)(10)(11), the quality of the scoring function (12,13), the choice of docking pocket, and finally, the availability of a relevant assay to test the virtual screening candidates.…”
mentioning
confidence: 99%
“…A recent case study by Muthas et al indicated that post-filtering with pharmacophores was shown to increase enrichment rates in their investigated targets compared with docking alone [6] . Several studies have been performed to assess various DBVS methods and compare which docking programs are the most successful in identifying active hits [7][8][9][10] . The conclusion is that no docking program may outperform other docking programs for all the tested targets, and the performance of each tested docking program is highly dependent on the nature of the target binding site [5] .…”
mentioning
confidence: 99%
“…Molecular docking is a powerful computational tool that can predict the interaction energy between two molecules (receptor and ligand) and determine which orientation of a ligand would form the lowest energy complex within the receptor's binding pocket [17][18][19][20][21] . In the Surflex docking methodology, Hammerhead's empirical scoring function is paired with a molecular similarity method to generate putative poses of ligand fragments.…”
Section: Introductionmentioning
confidence: 99%